Always Checking: Constant Connectivity and Fear of Missing Out among Generation Z Social Media Users - Fitri Norhabiba; Hasna Nur Lina; Mutiah (Jogjakarta Communication Conference (JCC), 2026)
Social media's rapid proliferation has engendered a pervasive culture of constant connectivity, particularly among Generation Z—digital natives immersed in hyper-connected environments from birth. Although perpetual online presence facilitates instantaneous communication and information access, it simultaneously precipitates psychological distress, including fear of missing out and digital anxiety. This study rigorously examines the causal relationship between constant connectivity and FOMO among Generation Z social media users, addressing a critical gap in understanding the emotional toll of digital nativity. A quantitative survey of 130 university students in Indonesia, was analyzed using Partial Least Squares Structural Equation Modeling, which robustly delineates structural paths and causal influences among latent constructs. Empirical results unequivocally confirm that constant connectivity exerts a significant positive effect on FOMO, with path coefficients indicating strong predictive power. A substantial majority (more than 70%) of respondents exhibited compulsive notification-checking and persistent online vigilance—emblematic of an entrenched "always-on" digital imperative. Correspondingly, prevalent reports of acute anxiety arising from disconnection or missing peer updates substantiate heightened emotional vulnerability. These findings compellingly demonstrate how unrelenting connectivity pressures amplify FOMO, eroding psychological well-being and distorting social perceptions. From a communication vantage point, this illuminates the transformative—and often maladaptive—role of digital platforms in reshaping Generation Z's behavioral norms and affective responses. By furnishing novel empirical evidence on these dynamics, the study advances digital communication scholarship and urgently advocates evidence-based interventions to foster healthier, more balanced social media engagement. Furthermore, the study provides a strategic framework for developers and policymakers to mitigate the deleterious psychological effects inherent in current platform design architectures. Future research should investigate the long-term cognitive implications of these habitual engagement patterns, particularly regarding degradation of attention span and sleep quality.